An evaluation of the outcome metric 'days alive and at home' in older patients after hip fracture surgery. (30th April 2022) - Wu, A.; Fahey, M. T.; Cui, D.; El‐Behesy, B.; Story, D. A.
Summary: 'Days alive and at home' is a validated measure that estimates the time spent at home, defined as the place of residence before admission to hospital. We evaluated this metric in older adults after hip fracture surgery and assessed two follow‐up durations, 30 and 90 days. Patients aged ≥ 70 years who underwent hip fracture surgery were identified retrospectively via hospital admission and government mortality records. Patients who successfully returned home and were still alive within 90 days of surgery were distinguished from those who were not. Regression models were used to examine which variables were associated with failure to return home and number of days at home among those who did return, within 90 days of surgery. We analysed the records of 825 patients. Median (IQR [range]) number of days at home within 90 days (n = 788) was 54 (0–76 [0–88]) days and within 30 days (n = 797) it was 2 (0–21 [0–28]) days. Out of these, 274 (35%) patients did not return home within 90 days and 374 (47%) within 30 days after surgery. Known peri‐operative risk‐factors such as older age, pre‐operative anaemia and postoperative acute renal impairment were associated with failure to return home. This study supports days alive and at home as a useful patient‐centred outcome measure in older adults after hip fracture surgery. We recommend that this metric should be used in clinical trials and measured at 90, rather than 30, postoperative days. As nearly half of this patient population did not return home within 30 days, the shorter time‐period catches fewer meaningful events.